The effect of welding line heat-affected-zone on the formability of tube hydroforming process. Issue 3 (August 2016) - ChiuHuang, Cheng-Kai; Hsu, Cheng-En; Lee, Ping-Kun
Abstract: Tube hydroforming has been used as a lightweight design approach to reduce CO2 emission for the automotive industry. For the high strength steel tube, the strength and quality of the welding line is very important for a successful tube hydroforming process. This paper aims to investigate the effect of the welding line's strength and the width of the heat-affected zone on the tube thinning during the hydroforming process. The simulation results show that both factors play an important role on the thickness distribution during the tube expansion.